Removal of zinc ions from model wastewater using electrodeposition - Dušek, Libor; Kočanová, Veronika (Slovenská spoločnosť chemického inžinierstva, 2016)
The present study deals with the electrochemical treatment of the wastewater generated from viscose fibres industry. Suitable process for electrochemical treatment of rayon wastewater is electrodeposition. Process is achieved by passing an electric current through a solution containing dissolved metal ions. Electrodeposition is the process which leads to the deposition of a metallic coating on a cathode in an electrochemical cell. Zinc has a standard reversible potential E° = - 0.76 V (standard hydrogen electrode (SHE)) at 25 °C that is more negative than that of iron (Fe/Fe2+ = - 0.44 V/SHE. Current density 5 mA/cm2 appears to be too low for satisfactory rate of electrodeposition, but current density only 10 or 20 mA/cm2 provides, after 16 h, 76.5% resp. 92% yield of regenerated zinc and all at current efficiency 27.2 kWh/m3 resp. 41.4 kWh/m3. It leads to conclusion that electrodeposition for regeneration of zinc from wastewater generated by the production of viscose fibres is a perspective technology. It is preferred to work at not adjusted pH of washing water (pH = 2.5) and low current density. But it is a little bit difficult in terms of capacity of needed equipment.
Odstraňování ionů zinku z modelových odpadních vod pomocí elektrrodepozice
Keywords: electrodeposition of zinc; model waste water with zinc ions; regeneration of zinc; elektrodepozice zinku; modelové odpadnívody se za2+ iony; regenerace zinku